Spearman correlation coefficient (rs) between echocardiographic measurements (i.e., left atrial:aortic root diameter; LA:Ao), markers of loss of GI barrier function (i.e., lipopolysaccharide; LPS), and cardiac (i.e., troponin) and systemic (i.e., cytokines) inflammation in 36 dogs with untreated myxomatous mitral valve disease (MMVD). - Maria C. Jugan (18928389) (2025)
Spearman correlation coefficient (rs) between echocardiographic measurements (i.e., left atrial:aortic root diameter; LA:Ao), markers of loss of GI barrier function (i.e., lipopolysaccharide; LPS), and cardiac (i.e., troponin) and systemic (i.e., cytokines) inflammation in 36 dogs with untreated myxomatous mitral valve disease (MMVD).